Complete Genomic Analysis of a Kingdom-Crossing Klebsiella variicola Isolate - Guo, Yatao; Zhai, Yao; Zhang, Zhao; Li, Daixi; Wang, Zhanwei; Li, Jingquan; He, Zilong; Hu, Songnian; Kang, Yu; Gao, Zhancheng (Frontiers in Microbiology, 2018)
Bacterial isolate X39 was isolated from a community-acquired pneumonia patient in Beijing, China. A phylogenetic tree based on rpoB genes and average nucleotide identity data confirmed that isolate X39 belonged to Klebsiella variicola. The genome of K. variicola X39 contained one circular chromosome and nine plasmids. Comparative genomic analyses with other K. variicola isolates revealed that K. variicola X39 contained the most unique genes. Of these unique genes, many were prophages and transposases. Many virulence factors were shared between K. variicola X39 and Klebsiella pneumoniae F1. The pathogenicity of K. variicola X39 was compared with that of K. pneumoniae F1 in an abdominal infection model. The results indicated that K. variicola X39 was less virulent than typical clinical K. pneumoniae F1. The genome of K. variicola X39 also contained some genes involved in plant colonization, nitrogen fixation, and defense against oxidative stress. GFP-labeled K. variicola X39 could colonize maize as an endophytic bacterium. We concluded that K. variicola X39 was a kingdom-crossing strain.